PERANCANGAN SISTEM INFORMASI PERMAK BUSANA BERBASIS WEB - Muhammad Azcha Panghudi Luhur (2023)
The Web-Based Fashion Alteration Information System is a platform designed to facilitate the process of clothing alterations or tailoring online. This system allows users, both customers and tailors, to interact and transact efficiently through a user-friendly web interface. Key features include online ordering, design selection, fabric selection, and communication between customers and tailors. The system also enables customers to monitor order status and obtain estimated completion times. Analytical capabilities are also integrated into the system to assist business owners in monitoring tailor performance, managing fabric inventory, and analyzing customer preferences. Customer and tailor information security is a top priority, so the system utilizes data encryption and robust authentication systems. By using web-based technology, this system can be accessed from various devices, including computers and mobile devices, allowing for greater flexibility and accessibility. With the implementation of this Web-Based Fashion Alteration Information System, it is expected that the clothing alteration process will become more efficient, transparent, and satisfying for all parties involved.